Masseter inhibitory reflex threshold: a novel technique for electrophysiological investigation of trigeminal nerve lesions - Haßfeld, Stefan; Schuchardt, Volker; Geisler, Hartmut; Meinck, Hans-Michael (Journal of the neurological sciences, 1995)
The masseter inhibitory reflex was investigated in 60 healthy volunteers, in 38 patients with trigeminal nerve branch lesions in the majority due to dental surgery, and in 9 patients with facial sensory loss and weakness caused by brain hemisphere lesions. The reflex threshold (TR) was almost symmetric both in normal subjects and in the patients with hemisphere lesions. In peripheral trigeminal hypaesthesia, elevation of TR on the lesioned side proved the most sensitive electrophysiological parameter. There was, moreover, some correspondence between the degree of sensory loss in hypaesthesic skin areas and elevation of TR, and recovery from the lesion was associated with TR normalization. Supratentorial lesions, in contrast, may influence the reflex pattern rather than reflex excitability.
Elektronische Reproduktion der Druck-Ausgabe 16. Dezember 1999
Gesehen am 22.07.2025